1992
DOI: 10.3109/13682829209029424
|View full text |Cite
|
Sign up to set email alerts
|

Language screening in preschool Chinese children

Abstract: SThe incidence of language delay in Chinese preschool children was studied by a stratified proportional sampling of all 3 year olds in Hong Kong. The Developmental Language Screening Scale (DLSS) devised for use with Cantonese speaking children was used to identify children with language delay. Of 855 children sampled in the stage I screening procedure, 4%, 2.8% and 3.3% were identified as having delay in verbal comprehension, expression or both respectively. The stage II clinical diagnostic study included a r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
25
3
1

Year Published

2005
2005
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(32 citation statements)
references
References 28 publications
3
25
3
1
Order By: Relevance
“…Particularly for speech and language impairments, the prevalence rate in Hong Kong is less than one tenth of that in the US. Independent academic research conducted in Hong Kong has indicated prevalence rates ranging from 3.35 to 4% for language impairments [3] and from 9.7 to 12.6% for dyslexia (a key diagnostic criterion for specific learning disability) [4]. The magnitude of these prevalence rates was similar to that found in the US governmental statistics.…”
Section: The Development Of Inclusive Educational Services In Hong Kongsupporting
confidence: 65%
“…Particularly for speech and language impairments, the prevalence rate in Hong Kong is less than one tenth of that in the US. Independent academic research conducted in Hong Kong has indicated prevalence rates ranging from 3.35 to 4% for language impairments [3] and from 9.7 to 12.6% for dyslexia (a key diagnostic criterion for specific learning disability) [4]. The magnitude of these prevalence rates was similar to that found in the US governmental statistics.…”
Section: The Development Of Inclusive Educational Services In Hong Kongsupporting
confidence: 65%
“…9 For preschool-aged children, 2 to 4.5 years old, studies that evaluated combined speech and language delay have reported prevalence rates ranging from 5% to 8%, 10,11 and studies of language delay have reported prevalence rates ranging from 2.3% to 19%. 9,[12][13][14][15] Untreated speech and language delay in preschool children has shown variable persistence rates (from 0% to 100%), with most studies reporting 40% to 60%. 9 In 1 study, two thirds of preschool-aged children who were referred for speech and language therapy and given no direct intervention proved eligible for therapy 12 months later.…”
mentioning
confidence: 99%
“…However, the present study does not agree with the prevalence rates revealed by Wong et al . () for preschoolers and with Hannus et al . () who gave relatively lower prevalence rates as compared with the above studies.…”
Section: Discussionmentioning
confidence: 64%